A clinical study of acute intestinal obstruction in adults-based on etiology, severity indicators and surgical outcome - Tiwari, Saurabh J.; Mulmule, Rajiva; Bijwe, Varsha N. (International Journal of Research in Medical Sciences, 2017)
Background: Patients with bowel obstruction still represent some of the most difficult and vexing problems that surgeons face today. While the adage, “never let the sun rise or set on a bowel obstruction” remains true, there has been a trend towards selective non-operative management of this problem. Aims and objectives were to study the various causes and modes of presentation of intestinal obstruction and to evaluate the importance of different severity indicators of obstruction with early recognition, diagnosis and thus timely abdominal exploration. Methods: 2 years prospective study conducted in PDMMC college, Amravati, Maharashtra, India, from September 2013 to September 2015. Each intestinal obstruction patient was evaluated with specific severity indicators, scored and then analyzed. Results: The commonest cause of intestinal obstruction in adults in this study series was adhesions in 33.33% cases. Other causes were mesenteric ischaemia, i.e. 7 (11.67%), Koch’s abdomen, i.e. 5 (8.33%), sigmoid volvulus, i.e. 5 (8.33%) and carcinoma, i.e. 5 (8.33%). Resection anastomosis was most commonly performed procedure in 45.7 % cases, followed by adhesiolysis in 14% patients. 66.66% patients having a score less than 3 were managed conservatively, 95.83 % having a score of 3 or more where operated on. Conclusions: The evaluation of patients endeavours not only to confirm the diagnosis but also to determine the need for and timing of surgery. Certain severity indicators and scoring systems can help to optimize this timing of surgery and prevent mortality.